Effect of Lead Nitrate on the Haematological Parameters of Channa punctatus - Dube, K.V; Magar, R.S (International Multidisciplinary Research Journal, 2013)
The present investigation deals with effect of heavy metal lead nitrate on haematological parameters of Channa punctatus. Lead nitrate induced significant changes at sub-lethal concentration during short term and long term exposure in haematology. The results revealed a decrease in parameters like RBC, WBC and Hb at short term exposure while WBC increases during long term exposure